La recusación heideggeriana de la teología natural - Filippi, Silvana (2002)
Heidegger rejects the idea of a christian philosophy, as long as he considers that the notion of God, set by the traditional Metaphysics, does not result compatible with “the divine God". On the contrary, the thinking of the being, as the philosopher of Freibourg understands, is proposed by him as an approach to the manifestation of the sacred, and in the end of God itself. This paper tries to show how the consideration of faith and reason as incompatible positions is based not only in some important misconceptions supported by Heidegger as regards the precedent Metaphysics, but also it may be unable to provide to the becoming thinking the chance to achieve a more faithful approximation to God.